Towards self-adaptation in DiffServ-GMPLS network for video-conferencing services. (7th July 2008) - Moungla, Hassine; Krief, Francine
The recently developed H.264 video standard achieves efficient encoding over a bandwidth ranging from a few kilobits per second to several megabits per second. Hence, transporting H.264 video is expected to be an important component of many networks multimedia services. However, due to lack of QoS support reaction networks, the basic GMPLS network management is not sufficient to deliver real-time traffic. The delivery should be augmented by appropriate mechanisms to adjust the QoS parameters. In this paper we address H.264 video transmission over GMPLS networks by proposing a robust policy based control architecture that leverages the inherent H.264 error resilience tools.